Pilot Study on the Cost of Some Oncohematology Diseases in Bulgaria - Tachkov, Konstantin; Kamusheva, Maria; Mitov, Konstantin; Doneva, Miglena; Petrova, Guenka (Frontiers in Public Health, 2019)
The goal of the current study is to perform a pilot study of the cost of some oncohematology diseases in Bulgaria. This is a pilot broader burden of disease research. The official report of the National health insurance fund provided information about the total expenditures paid for medicines, ambulatory services, and hospitalizations in 2015 and 2016. To evaluate the costs from a patient perspective, an internet inquiry was organized with the support of the patient organization. The inquiry contained questions regarding the patients’ demography, type of oncohematology disease, year of diagnosis, quality of life (EuroQol v5D), and additional out of pocket expenditures. Quality of Life data were statistically analyzed and Kruskal-Wallis analysis of variance was performed. From 2015 to 2016 the number of patients with oncohematological diseases decreased by approximately 3000 people. Less than 30% were hospitalized and the hospitalization cost decreased, but the cost for medicines increased by nearly 1.5 million Euros. Cost for medicines almost tripled the hospitalization cost. The reported mean quality of life was 0.749 (SD 0.203). There was positive correlation between QoL and current disease state (p=0.008) and age (p=0.025). 42% reported to have additional expenditures related to their oncohematology disease, 22% reported other expenditures (diet, change of everyday habits etc.) and 42% reported to have productivity loses due to loss of employment or change of work, 44% of the respondents reported additional payment for medicines for concomitant diseases. Thus, the total cost (public funds and patients) accounted for 37,708,764 Euro. Despite the high public expenditures, the indirect costs due to productivity loses are higher. Costs for medicines are higher than costs of inpatient treatment, but this tendency is observed in all European countries. The increases in the costs of medicines are compensated by reduced costs of hospitalization. Despite their higher costs, newer medicines are an effective and reasonable investment from a societal perspective. Currently the higher levels of copayment increase the burden on the patients.